Sistemas de informação de marketing nas empresas industriais de grande porte de Fortaleza - Nascimento, Pablo Carvalho de Sousa (2009)
Advances in information technology and development of information systems provide an environment conducive to the operation of Information Systems Marketing systems that are able to collect data, process it and generate from these, the information required on the internal environment and outside the organization. The use of these systems has become increasingly necessary in organizations because its ability to generate timely information and provide managers with information for decision making. By applying the questionnaire sought to know the reality of using these systems in the major industries of Fortaleza. Data collection occurred through the application of a questionnaire. in which the identification of the use and importance of marketing information was measured by a Likert scale seeks to analyze the position of manager. We also sought to identify the main sources of information used by managers in decision-making and also know the manager's perception of the benefits arising from the use of Information Systems Marketing in organizations. The results indicate that companies still do not have Information Systems Marketing formal deployed, but indicate that managers recognize the importance and need for them in decision-making. It can also identify the position of the companies surveyed in relation to the micro, macro environment of marketing activities, records and system of decision support. Additionally, the results have produced a series of hypotheses about SIM, worthy of consideration in future studies.